Delivering on open data: Current practices in data sharing, and challenges ahead! - Oefelein, Timon (Septentrio Conference Series, 2018)
Watch the VIDEO. The case for sharing research data has been strongly made in many parts of the world, but noticeably so in Europe. Open access to research data delivers more value for every funding Euro by enabling data reuse and reducing unnecessary duplication of research. Further, open data can help speed the pace of discovery and allows for reproducibility studies. The European Commission has set out a clear vision for open data in their Horizon Europe proposal. Yet in 2018 only about half of research data are shared, according to surveys of researchers, and a much smaller proportion are shared openly or in ways that maximise discoverability and reuse. Whilst policy implementation remains critical to the uptake of data sharing, this must be joined by greater support and education for researchers, and faster, easier routes to sharing data optimally. We also need to make it worth a researcher’s time to share their data. Starting with the case for better data practice, this talk showcases the findings of one of the largest author surveys of its kind on current practices, attitudes and perceptions in data-sharing at the point of scholarly publication. The survey, carried out by Springer Nature in 2018, is based on over 7700 responses from academic researchers - at various levels of their career – in Europe, Asia, America, and Australasia. Responses are from across all subject areas. The resulting data provides a valuable insight into how, where, and why data is currently shared and what the main obstacles to sharing it are. The talk identifies the most “critical areas” – as borne out of the survey findings – that need to be tackled with top priority if we are to accelerate the speed and scope of data-sharing. In closing, we therefore ask – how can we better work together across research libraries, institutions, funders, governments, and publishers, to address and action these “critical areas”? Indeed, it is only by working together that we can unlock the huge potential of research data, namely to improve our knowledge, to address the grand societal challenges, and to help solve some of the most pressing problems in science today.